2005
DOI: 10.1002/qua.20620
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of weakly interacting molecular systems using the virial theorem

Abstract: ABSTRACT:In this work we examine some H-bonded systems using the method of separated molecular orbitals (SMOs) at the Hartree-Fock level. Several geometryoptimized configurations of the water hexamer were chosen for the study. The energetic components for the monomers in the whole structures and also in the contributing subunits of the supersystems were calculated. Five different basis sets were applied and the fulfillment of the virial theorem was assessed. A two-parameter geometry dependence of these energet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, a similar balance is required between the supersystem and their subsystems. This requirement has been analyzed in our previous work [10] and pointed out to hold for the water dimer. Obviously, in the case the weakly interacting structure is composed from several different molecules, the −V/T quantity should be close to 2.0 for each subsystem (and for the supersystem, too).…”
Section: The Partitioned Energetic Quantities and Their Derivativesmentioning
confidence: 92%
See 1 more Smart Citation
“…On the other hand, a similar balance is required between the supersystem and their subsystems. This requirement has been analyzed in our previous work [10] and pointed out to hold for the water dimer. Obviously, in the case the weakly interacting structure is composed from several different molecules, the −V/T quantity should be close to 2.0 for each subsystem (and for the supersystem, too).…”
Section: The Partitioned Energetic Quantities and Their Derivativesmentioning
confidence: 92%
“…Several energetic terms and the derived (−V/T) quantities have been studied for some hexamer water clusters using various basis sets by the above described partitioning scheme [10,11]. The results have shown that the partitioned kinetic energy terms derived for the contributing monomers have significant differences for a water molecule with proton donor or proton acceptor nature in the water hexamers.…”
Section: The Partitioned Energetic Quantities and Their Derivativesmentioning
confidence: 99%